The dual principal leadership structure in international schools’ management: a study based on two schools in Mainland China - Li, Jiayi (Frontiers in Education, 2025)
International schools—a relatively recent type of K-12 educational institution in Mainland China—have expanded rapidly in response to market demand. These profit-oriented schools use English as the primary language of instruction and offer international curricula, factors that heighten management complexity. Operating within the constraints of a socialist system presents additional challenges. This qualitative case study examines the management structures and challenges of such schools, focusing on the dual principal leadership model commonly adopted in these institutions. Data were collected from May to June 2024 through in-depth interviews with eight school leaders across two international schools in Guangzhou and Shenzhen—economically prosperous cities and key hubs for international school growth. Data analysis employed a three-level coding process to identify patterns and themes. Findings indicate that the adoption of the dual principal leadership structure is driven by the schools’ diverse cross-cultural characteristics and the complexities of localized operations, while also revealing tensions between marketing and educational logics in school management. The study proposes strategies to strengthen this leadership model and highlights considerations for its effective implementation. Theoretically, the research extends the application of institutional logics theory to the governance of international schools in market contexts, offering insights into leadership design and decision-making in internationalized school settings where cultural hybridity and institutional pluralism are prevalent.